Time-Varying Impact of Economic Growth on Carbon Emission in BRICS Countries: New Evidence From Wavelet Analysis - Xiang, Lijin; Chen, Xiao; Su, Shuling; Yin, Zhichao (Frontiers in Environmental Science, 2021)
Carbon emission leads to environmental and social consequences, which could be severe in the emerging economies. Due to the dilemma of emission and economic expansion, it is necessary to achieve more comprehensive understanding of the dynamic relationship between economic growth and carbon emission. Multivariate Wavelet analysis is introduced in addition to the decoupling analysis for BRICS countries. The decoupling analysis detects an obvious trend of economic growth decoupling from carbon emission in China, and generates mixed results for the other countries. Estimates of wavelet coherency suggest that BRICS countries have experienced different kinds of structural changes in growth-emission nexus. Results of partial phase-difference and wavelet gain implies that different resource endowments and growth paths lead to varied impact of economic growth on carbon emission and time-varying characteristics of the causality relationship over different frequencies. Energy structure and trade openness matter for anatomizing this time-varying relationship. To succeed in the fight against climate change, the policy makers need to pay serious attention to the dynamic impact of economic growth, energy structure and trade openness on carbon emission.